Overview of Community Landslide and Flood Vulnerability in Northwestern Rwanda - Clemence Idukunda; Sabine Henry; Emmanuel Twarabamenye; Florence De Longueville (European Scientific Journal, ESJ, 2024)
Northwestern Rwanda is highly susceptible to landslides and floods. Understanding the community's vulnerability to these hazards is crucial for implementing effective mitigation measures. This study assesses the vulnerability of communities in Northwestern Rwanda through a household survey and interviews with key informants conducted in May-June 2022. A total of 158 households were randomly sampled from the study area to ensure representation across various socio-economic backgrounds and geographic locations. In addition, 22 key informants were randomly selected from among local leaders, including heads of cells and officials responsible for disaster risk reduction and management at district and sector levels. This approach was designed to complement the data collected from the households. The results indicate that landslides and floods are the primary hazards affecting the community in the study area. Agriculture livestock, and small businesses are the main income sources impacted by these hazards, with 88.7% of respondents heavily dependent on agriculture. Dependence on agriculture as the sole source of income (88.7%), low educational attainment (61.4%), low economic status (56.3%), and proximity to rivers or steep slopes were identified as significant contributors to community vulnerability. To mitigate landslide and flood risks in the study area, several preventative measures are being implemented. These include the relocation of residents from hazardous areas to safer locations, repairing and constructing rainwater drainage systems in flood-prone areas, development of radical terraces on hillsides, building of water channels, and establishment of early warning systems. Despite these efforts, a notable 69.5% of respondents have mentioned insufficient financial resources as a principal barrier to achieving effective implementation. This study provides valuable insights for policymakers, underscoring the imperative for robust policies and programs aimed at mitigating the impacts of landslides and floods. The study recommends (1) increasing financial allocations to local administrative entities to bolster the execution of preventative measures against landslides and floods, and (2) enhancing educational initiatives and economic prospects to diminish community vulnerability. Addressing these areas is crucial for ensuring the well-being of inhabitants in the face of landslides and floods.